Increasing the Quality of Education by Maximizing the Role of Educational Supervision in MIS YPI Batang KUIS - Leli Hasanah Lubis; Ali Sadikin Ritonga; Mulkan Darajat; Yuslinda Yuslinda; Sri Hayati Damanik (Edumaspul: Jurnal Pendidikan, 2023)
This research discusses the Quality of Education which is something that must be improved by every Educational Institution, especially the MIS YPI Batang Kuis, educational supervision can improve the professional and technical abilities of teachers, principals and other school personnel so that the educational process in schools is of higher quality. And the most important thing is that educational supervision is carried out on the basis of cooperation, and the method is more humane. This research method is descriptive qualitative, the location of this research is the MIS YPI Batang Kuis. The results of this study are that educational supervision at the MIS YPI Batang Kuis has a role in providing convenience and helping teachers develop their potential optimally. Judging from the function of supervision as follows: (a). As a coordinator he can coordinate teaching and learning programs, staff member assignments various different activities among MIS YPI Batang Kuis teachers. (b). As a consultant he provided assistance, together with consulting the problems experienced by MIS YPI Batang Kuis teachers both individually and as a group. In accordance with the use of supervision techniques. (c). As a group leader he can lead a staff of teachers in developing the potential of the group, while developing curriculum, subject matter and the professional needs of teachers together. (d). As an evaluator he helps the MIS YPI Batang Kuis teachers in assessing results and learning processes, can assess the curriculum that is being developed. He must also learn to look at himself. Judging from its definition and function, supervision plays a very important role in improving the quality of education at the MIS YPI Batang Kuis.